Decree With Legislative Content in Comparative Constitutional Law - Manili, Pablo Luis (As-Siyasi: Journal of Constitutional Law, 2024)
This study examines the regulation of Emergency and Urgency Decrees (DNU) in various international constitutions to identify common patterns and differences among them. The research aims to conduct a comparative analysis of DNU regulations in various international constitutions, identifying common patterns, similarities, and differences. The primary focus is to understand how different countries regulate the use of DNUs, including approval procedures, material limitations, and legislative oversight mechanisms. This study employs normative juridical research with a statutory and comparative approach. The countries compared in this study include the United Kingdom, the United States, Paraguay, Prussia, Austria, Spain, Italy, Sweden, Brazil, Colombia, Peru, Ecuador, and Argentina. The data used are secondary data comprising primary legal materials, including the constitutions of the respective countries and their statutory regulations. Secondary legal materials consist of research articles and journals, while tertiary legal materials include dictionaries. The results indicate that although many constitutions do not explicitly regulate DNUs, parliamentary systems are more likely to have DNU-related regulations compared to presidential systems. All constitutions that regulate DNUs require immediate approval by the legislature and set specific time limits for this process. Some countries impose strict limitations on the material that can be regulated through DNUs, ensuring that fundamental rights and government structures are not affected. The study concludes that stringent legislative oversight is necessary to prevent the misuse of executive power in the use of DNUs, and balancing the need for swift action with the protection of human rights is crucial for the effectiveness and accountability of DNUs.